Effectiveness Of HF-Care Educational Media on Self-Care Among Patients with Heart Failure: A Quasi-Experimental - Amalia, Irma Nur; Ardianti, Putri Yudhi; Setiawan, Deris Riandi; Daryaman, Usan (Chakra Brahmanda Lentera Institute, 2026)
Background: Heart Failure (HF) remains a major cause of morbidity, mortality, and recurrent hospitalization, often associated with inadequate self-care. Although educational interventions can support HF self-management, evidence on HF-Care educational media in the Indonesian healthcare context remains limited. This study evaluated the effectiveness of HF-Care educational media on self-care among patients with heart failure. Methods: A two-week quasi-experimental two-group pretest–posttest study following the TREND guideline was conducted at an Indonesian military teaching hospital in Bandung. Forty-six patients with HF were recruited using purposive sampling and allocated to an intervention group or control group, with 23 participants in each group. The intervention group received HF-Care educational media in addition to usual care, while the control group received usual care only. Self-care was measured using the Self-Care of HF Index Version 7.2. Data were analyzed using descriptive statistics, paired-samples t-tests, and independent-samples t-tests. Results: Self-care improved in both groups, with greater improvement in the intervention group. The intervention group had significantly higher posttest self-care scores than the control group, with a mean difference of 27.00 points (95% CI: 21.80–32.20; p < 0.001) and a very large effect size (Cohen’s d = 3.14).. Conclusion: HF-Care educational media may serve as an effective evidence-based nursing intervention to improve self-care among patients with heart failure. Future multicenter studies with larger samples, randomized designs, and longer follow-up are needed to confirm its sustainability and broader applicability.